Discover Crimes against Humanity as Gross Violations of Human Rights: International and Indonesia Perspectives - Gde Made Swardhana (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2021)
The human rights law is not identical with international humanitarian law. This article attempts to explore both the relation and the difference between gross human rights violation and violation of international humanitarian law. While, for Indonesia context, crimes against humanity was arranged in the Human Rights Court Law, however, it is still raise discourses related with the limitation of crime against humanity that different with international law instruments, and it also raises problem for Judges and Human Rights Court to define the crimes against humanity as the legal ground for several gross violation of human rights that adjudicate within this framework. This article use normative legal research method to conduct, analyze, and arrange crime against humanity formulation with statutory law approach, legal conceptual approach, and legal cases approach. This article concluded with the limitation that highlighted whether gross human rights violation can be prosecuted and punished using international humanitarian law. This article also stressing normative and conceptual aspect related with development of crimes against humanity, its element of crime and its application by judicial system.